2005
DOI: 10.1007/s11274-005-0078-x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterisation of Keratinase from a Thermotolerant Feather-degrading Bacterium

Abstract: Isolation and identification of a thermotolerant feather-degrading bacterial strain from Thai soil as well as purification and properties of its keratinase were investigated. The thermotolerant bacterium was identified as Bacillus licheniformis. The keratinase was purified to homogeneity by three-step chromatography. The purified enzyme exhibited a high specific activity (218 U mg )1 ) with 86-fold purification and 25% yield. The enzyme was monomeric and had a molecular mass of 35 kDa. The optimum pH and tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
44
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 38 publications
10
44
1
1
Order By: Relevance
“…It has been suggested that inhibition by Hg 2+ is not just related to binding of the thiol groups but may be a result of an interaction with tryptophan residues or with the carbonyl group of amino acids in the enzyme [37,38]. C. echinulata keratinase was inhibited by PMSF, thus it may be a serine protease.…”
Section: + Keratinase Inhibition By Hgmentioning
confidence: 99%
“…It has been suggested that inhibition by Hg 2+ is not just related to binding of the thiol groups but may be a result of an interaction with tryptophan residues or with the carbonyl group of amino acids in the enzyme [37,38]. C. echinulata keratinase was inhibited by PMSF, thus it may be a serine protease.…”
Section: + Keratinase Inhibition By Hgmentioning
confidence: 99%
“…Ultrafiltration has been applied in the purification of keratinases only intended to concentrate the enzyme for the next purification step [7,8,[27][28][29]. However, it is observed that the values found in the cited works are lower than those found in this study that use just one step.…”
Section: Concentration and Purification Of Keratinase Bymentioning
confidence: 64%
“…Cheng et al [8] and Suntornsuk et al [29] also used a membrane MWCO of 10 kDa for keratinase concentration. Cheng et al [8] characterized the keratinase produced by Bacillus licheniformis PWD-l produced with feather powder.…”
Section: Concentration and Purification Of Keratinase Bymentioning
confidence: 99%
“…This method is very laborious and time consuming but separation of protein is very reliable. Ultra filtration is another method for the separation of proteins of different molecular weight [26] . Proteins having molecular weight higher than or equal to 100kDa were used.…”
Section: Purification Of Protease Enzymementioning
confidence: 99%
“…Over the last few decades leather industry is based on large scale chemicals treatment which created worldwide environmental hazards. Enzymatic dehairing in tanneries has been envisaged as an alternative to sulfides [26] . Use of enzymes for industrial processing has received considerable attention in recent years owing mainly to environmental concerns [10] .…”
Section: Introductionmentioning
confidence: 99%